A collaborative commerce framework for the real estate industry. (1st January 2003) - Selen, Willem
The internet is opening up new business opportunities for the real estate industry. It provides real estate companies with new ways to collaborate with service providers, gain customer and market information, and communicate with the customer in new ways to turn the industry into a customer-centric driven modus operandi. It also makes the real estate market more transparent, and hence more efficient. This, in turn, will create downward pressure on existing commission fees, create multiple revenue channels, and redefine the role of the agent as an intermediary. In order to move towards a more desirable one-stop shopping experience, real estate companies have to form closer relationships with various business players, thereby moving towards a collaborative commerce model. Such a model is outlined to show how it could work for the real estate industry. Whilst much more is to be done in implementing the total collaborative commerce model, some initial progress is being made in integrating website design features for one-on-one marketing, and in linking web-interface design and development with the enabling supply chain partners and information providers within the service value chain.